Triple progress

Algebra Level 3

( 1 + 2 3 + ( 2 3 ) 2 + ) + ( 1 + 3 4 + ( 3 4 ) 2 + ) + ( 1 + 4 5 + ( 4 5 ) 2 + ) = ? \left(1+ \frac 23 + \left(\frac 23\right)^2 +\cdots \right) + \left(1 + \frac 34 + \left(\frac 34 \right)^2 + \cdots \right) + \left(1 + \frac 45 + \left(\frac 45 \right)^2 + \cdots \right) = \, ?


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Aug 27, 2016

Relevant wiki: Geometric Progression Sum

S = ( 1 + 2 3 + ( 2 3 ) 2 + . . . ) + ( 1 + 3 4 + ( 3 4 ) 2 + . . . ) + ( 1 + 4 5 + ( 4 5 ) 2 + . . . ) = n = 0 ( 2 3 ) n + n = 0 ( 3 4 ) n + n = 0 ( 4 5 ) n = 1 1 2 3 + 1 1 3 4 + 1 1 4 5 = 3 + 4 + 5 = 12 \begin{aligned} S & = \left(1+ \frac 23 + \left(\frac 23\right)^2 + ...\right) + \left(1 + \frac 34 + \left(\frac 34 \right)^2 + ...\right) + \left(1 + \frac 45 + \left(\frac 45 \right)^2 + ...\right) \\ & = \sum_{n=0}^\infty \left(\frac 23\right)^n + \sum_{n=0}^\infty \left(\frac 34\right)^n + \sum_{n=0}^\infty \left(\frac 45\right)^n \\ & = \frac 1{1-\frac 23} + \frac 1{1-\frac 34} + \frac 1{1-\frac 45} \\ & = 3 + 4 + 5 = \boxed{12} \end{aligned}

Denton Young
Aug 26, 2016

By GP rule, first progression equals 3, second = 4, third = 5. 3 + 4 + 5 = 12

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...